2011
DOI: 10.1016/j.diff.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic membrane as an alternative source of stem cells for regenerative medicine

Abstract: The human amniotic membrane (HAM) is a highly abundant and readily available tissue. This amniotic tissue has considerable advantageous characteristics to be considered as an attractive material in the field of regenerative medicine. It has low immunogenicity, anti-inflammatory properties and their cells can be isolated without the sacrifice of human embryos. Since it is discarded post-partum it may be useful for regenerative medicine and cell therapy. Amniotic membranes have already been used extensively as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 123 publications
5
86
0
2
Order By: Relevance
“…Currently, they are both discarded as a waste of the labour, but they proved to contain large numbers of multipotent mesenchymal cells, which were supposed to feature intermediate characteristics between embryonic and adult stem cells [69]. The amnios has shown to bear adherent MSCs with classical pattern of molecular markers and multipotency (as shown by in vitro differentiation towards endodermal, mesodermal, and ectodermal lineages) [70]. These cells express cardiac-specific transcription factors (such as those belonging to GATA family), and MHC class I molecules HLA-A, -B, and -C. It has been demonstrated that these cells exert in vivo a differentiative potential towards cardiomyocytes and result in improved cardiac function [71,72].…”
Section: Human Umbilical Cord: the Hidden Po-tential Of A Discarded Tmentioning
confidence: 99%
“…Currently, they are both discarded as a waste of the labour, but they proved to contain large numbers of multipotent mesenchymal cells, which were supposed to feature intermediate characteristics between embryonic and adult stem cells [69]. The amnios has shown to bear adherent MSCs with classical pattern of molecular markers and multipotency (as shown by in vitro differentiation towards endodermal, mesodermal, and ectodermal lineages) [70]. These cells express cardiac-specific transcription factors (such as those belonging to GATA family), and MHC class I molecules HLA-A, -B, and -C. It has been demonstrated that these cells exert in vivo a differentiative potential towards cardiomyocytes and result in improved cardiac function [71,72].…”
Section: Human Umbilical Cord: the Hidden Po-tential Of A Discarded Tmentioning
confidence: 99%
“…The clinical applicability of AM has become increasingly important due to their low antigenicity and antimicrobial action as well as their ability to decrease exudate and adhesions, accelerate epithelialization, reduce local pain, act as a substrate for the growth of tissues, and so on [16][17][18][19] . These properties suggest that AM could be used as a biological dressing, thereby providing an alternative for chronic wound treatment and benefitting certain phases of the healing process including inflammation, granulation, epithelialization, and fibroplasia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to a transient improvement in body function by pharmaceuticals, stem cells may prevent or delay host cell death and restore injured tissues (Lindvall and Kokaia, 2006;Blurton-Jones et al, 2009;Kim and de Vellis, 2009). Mesenchymal stem cells (MSCs) have been isolated from several tissues, such as bone marrow, adipose tissue, umbilical cord blood, and the amniotic membrane (Pittenger et al, 1999;Díaz-Prado et al, 2011). Adipose tissue-derived MSCs (ADMSCs) have recently received attention as a promising source of cells for cell therapy.…”
mentioning
confidence: 99%
“…Adipose tissue contains hundreds of thousands of MSCs in each gram of fat (Sen et al, 2001), whereas BMMSCs in the bone marrow fraction constitute a mere 0.0001-0.01% of all nucleated cells (Pittenger et al, 1999). In particular, ADMSCs differentiate into several cell types (Constantin et al, 2009), and, unlike embryonic stem cells, are an ethically uncontroversial source for stem cell therapy (Díaz-Prado et al, 2011).…”
mentioning
confidence: 99%